Gestión asociada para el desarrollo local sustentable del Teuco-Bermejito - Francioni Modenes, María del Carmen (2001)
After a long period of vindicating claims and growing organization, the indigenous community TOBA achieved in 1999, the return of 150,000 hectares by the delivery, by the Government of the Province of Chaco, of the Community Title of land to the Association MEGUESOXOCm. This act of reparation to a community historically postponed, unleashes a series of consequences on the population settled in the Interfluve area, the most significant being the relocation of Creole settlers. To the tremendous difficulties that these families must face to achieve survival are now added the important tensions that emerge from the change in the legal status of the land, which turns part of the inhabitants, who occupied tax lands, into interlopers. Families, both Toba and Creole who, from the delivery of the community title occupy strips with specific destination (lands destined to the Creoles or securitized in favor of the aboriginal community) and must relocate; that is, they are subject to an involuntary relocation. It is necessary to clarify that the next population movements not only affect Tabas and Creole families in the area, but that there is even the possibility of the return of tabas who had emigrated from the Interfluve Teuco-Bermejito, today creditors of these lands. The anxiety for a future that is uncertain and exceeds the own capacities of the local population, added to the own climatic characteristics of the region, where there are negative effects and adversities derived from cycles of droughts and floods, in a context of economic crisis , which crosses the country and the province, explains that the inhabitants of the area are subject to a critical situation, emergency and uncertainty, which highlights the social urgency, and the need to build an adequate response. To face this complex situation and give a comprehensive response, the Province of Chaco forms the Provincial Mixed Commission that has launched a process of participatory and intersectional planning in order to design and implement a project that ensures the sustainability of the region and its inhabitants: the Teuco-Bermejito Interfluve Integrated Project. Within this process of participatory planning, a preparatory stage of sensitization of actors has been carried out and it is necessary to advance in the consensual design of the integrated project and its programs. The Change Project "Associated Management for the Sustainable Local Development of Teuco-Bermejito" provides essential elements for a process of this nature: appropriate methodologies and scenarios for the design of viable strategies, intersectoriality and participation. The formulation of the Teuco Bermejito Integrated Project and its programs then has an Ad-hoc Technical Assistance that facilitates the achievement of the results of this design stage and the consolidation of the local development process in which it is inserted.